The Suitability of Video Learning Media on Youtube with Poetry Writing Learning Materials Curriculum - Wicaksono, Harits Agung; Pristiwati, Rahayu (International Journal of Active Learning, 2021)
This research is motivated by the large number of video learning media teaching materials to write poetry texts taken from Youtube without any adjustment and filtering of the content contained. The purpose of this study was to analyze the results of the suitability of video learning media on Youtube with the curriculum of writing poetry in class X SMA. The method used in this research is descriptive qualitative with research data sources obtained from Youtube. The results of this study refer to the indicators of the suitability of writing poetry in the curriculum by paying attention to the building blocks, namely theme, diction, language style, image, structure, and appearance. The results of the analysis show that in the discussion of the poetry theme there are four videos that are in accordance with the 2013 revised curriculum. One of the videos did not describe the theme material in detail. The diction material is discussed in all videos analyzed by the researcher. Furthermore, the language style is presented in all videos with a variety of different explanations according to the development of each presenter. In the presentation of image material, only one video describes it in detail, namely the video entitled Poetry Writing Learning Videos. In the material physical and mental structure, the physical and mental structure of the poetry is described as a whole. These structures are conveyed in all the indicator points of this research analysis which are part of the physical and mental part of the poetry. In the form or typography presented in four videos explaining the lyrics, good, and characteristics.